ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH MELALUI ANALISIS RASIO KEUANGAN APBD KABUPATEN/KOTA DI INDONESIA SEBELUM DAN SESUDAH PENERAPAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 - Tama, Annafi Indra (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
This study aims to find out about the comparison of districts financial performance indicators in Indonesia and to determine whether there are differences in that before and after implementation of Law No.28/2009. In thisstudy, financial performance are valued by indicators of independence, the degree of decentralization, financialdependency areas, the effectiveness, efficiency, and contribution of local taxes and levies at 17 districts financialstatement. This study used audited district financial statement to proof the hypothesis. 2010 is claim as the priorperiod of application of the law, and 2012 as the year after the implementation. The analysis technique used inthis study is analytical study of district financial performance. Paired sample t-test with significance level of0.05 is used to test the hypothesis. The results show that there is significantly difference on district financialperformance. In the form of independence indicators, decentralization degree, efficiency of local taxes,contribution of local tax and levies are higher in the period before the implementation, but for financialdependency is lower in the period after implementation. In the other hand, there is no difference in the form ofdistrict financial effectiveness before and after implementation of the law.